Locked Traumatic Pisiform Dislocation: A Case Report - (:unkn) unknown (Lippincott Williams and Wilkins, 2019)
Case:A 32-year-old man presented to the emergency department with several carpal bone fractures and a locked distal pisiform dislocation after trauma. Treatment consisted of open surgical and reduction, osteosynthesis with a single Kirschner wire, and ligament repair. The patient's functional outcome was excellent, and his Mayo wrist score was 90 at 36 months after injury.Conclusions:Pisiform dislocations may be difficult to diagnose because anteroposterior and lateral radiographs may not be sufficient to visualize the injury. A 30° semisupinated wrist X-ray and computed tomography can be helpful. A satisfactory clinical result may be achieved if distal pisiform dislocations are detected early and managed surgically with open reduction and ligament repair. © 2019 BY THE JOURNAL OF BONE AND JOINT SURGERY, INCORPORATED.